Solid Carbon Dioxide Based Cryosurgical Device and Its Application for Stereotactic Brain Surgery - Kholyavin, Andrey I.; Nizkovolos, Vladimir B. (Problems of Cryobiology and Cryomedicine, 2014)
In the laboratory of stereotactic methods of IHB RAS there has been designed the cryosurgical device based on solid carbon dioxide as a cold source. This device was applied at neurosurgical clinic in stereotactic brain surgeries such as: punctate destructions of subcortical structures in therapy of epilepsy, Parkinson's disease and other chronic CNS diseases; multiposition cryodestructions of intracerebral tumours, localised in deep and functionally important brain compartments. Clinical results demonstrate the advantages of the device when exposed to brain tissue such as: the safety, controllability, easy handling, etc. As a result of cryodestruction application there was a significant increase in survival rate of patients with deep brain tumours previously considered as inoperable. Probl Cryobiol Cryomed 2014; 24(4):354-365.